Double-balloon endoscopic retrograde cholangiography can make a reliable diagnosis and good prognosis for postoperative complications of congenital biliary dilatation - Chiyoe Shirota (Nature Portfolio, 2021)
Abstract Bile duct and anastomotic strictures and intrahepatic stones are common postoperative complications of congenital biliary dilatation (CBD). We performed double-balloon endoscopic retrograde cholangiography (DBERC) for diagnostic and therapeutic purposes after radical surgery. We focused on the effectiveness of DBERC for the treatment of postoperative complications of CBD patients. Bile duct and anastomotic strictures and intrahepatic stones are common postoperative complications of congenital biliary dilatation (CBD). We performed double-balloon endoscopic retrograde cholangiography (DBERC) for diagnostic and therapeutic purposes after radical surgery. We focused on the effectiveness of DBERC for the treatment of postoperative complications of CBD patients. This retrospective study included 28 patients who underwent DBERC (44 procedures) after radical surgery for CBD between January 2011 and December 2019. Strictures were diagnosed as “bile duct strictures” if endoscopy confirmed the presence of bile duct mucosa between the stenotic and anastomotic regions, and as “anastomotic strictures” if the mucosa was absent. The median patient age was 4 (range 0–67) years at the time of primary surgery for CBD and 27.5 (range 8–76) years at the time of DBERC. All anastomotic strictures could be treated with only by 1–2 courses of balloon dilatation of DBERC, while many bile duct strictures (41.2%) needed ≥ 3 treatments, especially those who underwent operative bile duct plasty as the first treatment (83.3%). Although the study was limited by the short follow-up period after DBERC treatment, DBERC is recommended as the first-line treatment for hepatolithiasis associated with biliary and anastomotic strictures in CBD patients, and it can be safely performed multiple times.